PERBEDAAN KUALITAS TIDUR MAHASISWA PROGRAM STUDI ILMU KEPERAWATAN ANTARA KONDISI LAMPU MATI DENGAN KONDISI LAMPU HIDUP - Elisabet Sinaga, Ananda Tasya; Syafina Melati Azri; Siti Nurhadijah; Desni Theresia Butar-butar (Citra Internasional Institute, 2024)
Sleep quality is everyone's ability to maintain their sleep state and to get proper REM and NREM sleep stages (Khasanah & Hidayati, 2012). Objective: Identify differences in lights off and lights on students' sleep quality. Method: In this study the author used a quantitative type of study with a quasi-experimental design, the Instrument used in this study was Sleep Quality adapted from the Pittsburgh Sleep Quality Index (PSQI) and the questionnaire was tested for validity and rehabilitation. Results: Sleep quality in the most living lamp conditions in the bad category, namely in the 20-year-old group as many as 5 people (45.4%), 6-7 hours of sleep duration with good sleep quality as many as 5 people (45.4%), has a history of illness with good sleep quality as many as 5 people (45.4%). Meanwhile, in the 19 years old group, there are 7 people (36.8%), with a 6-7 hours’ sleep duration that has a good sleep quality of 8 people (42.1%), there is no history of diseases with a good sleep quality of 8 people (42.1%). Conclusion: The picture of lamp uses in Nursing Students in 2024 when sleeping with lights on is 11 people (36.6%), while lamp use when sleeping with lights off is 19 people (63.4%). The picture of the quality of sleep for Nursing Students in 2024, which has a good quality of sleep, is 22 people (73.4%), while the quality of sleep is 8 people (26.6%).